Implementasi Program Bakti Sosial Mahasiswa Kedokteran sebagai Upaya Pemberdayaan Masyarakat: (Studi Kegiatan Fakultas Kedokteran UMI Bersama BEM KBMFK Universitas Muslim Indonesia Tahun 2025) - Nasrudin Andi Mappaware; Irna Diyana Kartika Kamaluddin; Wawan Susilo; Faizul A; Andi Alamanda Irwan; M. Hamsah; Berry Erida Hasbi; Indah Lestari Daeng Kanang; Prema Hapsari Hidayati; Anna Sari Dewi; Dwi Anggita; Sidrah Darma; Nevi Sulvita Karsa; Zulfikri Khalil Novriansyah; Mohammad Reza Zainal Abidin; Muhammad Fauzul Azhim; Astra Budiati Nusrat; Muhammad Irsan Muflih Mundzir; Mufthiar Muhtar; Rizky Nurhumairah Sarifuddin; Wulan Purnamasyani S; Waode Inayatu Zahra Khairunnufus (Pusat Riset dan Inovasi Nasional, 2026)
The Grand Social Service (Bakti Sosial Akbar) organized by KBMFK-UMI is an initiative that reflects the academic community's empathy and care for society, especially those in need. The activity aims to express a sense of social responsibility by providing various services to the community. These services include health checks, education, blood donation drives, mass circumcision, Basic Life Support (BLS) training, and the distribution of the Susu Anak Negeri (SUSAN) program. Through these efforts, the event seeks to alleviate some of the burdens faced by local communities while promoting health awareness and knowledge. In addition to offering essential services, this event is designed to strengthen relationships among students, faculty members, and the local residents by fostering a spirit of togetherness and collaboration. The implementation of this community service activity is made possible by the full support of the academic community at the Faculty of Medicine, Universitas Muslim Indonesia, ensuring that all activities are carried out effectively and precisely. It is expected that the positive outcomes of this event will not only benefit the community but also contribute to building a stronger sense of social solidarity and cooperation among all involved.